Endogenous separations, wage rigidities and employment volatility - Mikael Carlsson; Andreas Westermark (Sveriges Riksbank, 2016)
We show that in micro data, as well as in a search and matching model with endogenous separations and rigid wages, separations and hence employment volatility are non-neutral to wage rigidities of incumbent workers. In contrast to when all wages are flexible, the standard deviation of unemployment in a model with rigid wages for incumbent workers (only) matches the standard deviation in the data. Thus, the degree of wage rigidity for newly hired workers is not a sufficient statistic for determining the effect of wage rigidities on macroeconomic outcomes in this class of models.
Keywords: J63; J64; E30; 330; Search and matching; Unemployment volatility puzzle; Wage rigidities; Job Destruction